Light-dimerization telechelic alginate-based amphiphiles reinforced Pickering emulsion for 3D printing. (1st January 2023) - Zhao, Xinyu; Yang, Shujuan; He, Furui; Liu, Haifang; Mai, Keyang; Huang, Junhao; Yu, Gaobo; Feng, Yuhong; Li, Jiacheng
Abstract: Functional Pickering emulsions that depend on the interparticle interactions hold promise for building template materials. A novel coumarin-grafting alginate-based amphiphilic telechelic macromolecules (ATMs) undergoing photo-dimerization enhanced particle-particle interactions and changed the self-assembly behavior in solutions. The influence of self-organization of polymeric particles on the droplet size, microtopography, interfacial adsorption and viscoelasticity of Pickering emulsions were further determined by multi-scale methodology. Results showed that stronger attractive interparticle interactions of ATMs (post-UV) endowed Pickering emulsion with small droplet size (16.8 μm), low interfacial tension (9.31 mN/m), thick interfacial film, high interfacial viscoelasticity and adsorption mass, and well stability. The high yield stress, outstanding extrudability (n1 < 1), high structure maintainability, and well shape retention ability, makes them ideal inks for direct 3D printing without any additions. The ATMs provides an increased capacity to produce stable Pickering emulsions with tailoring their interfacial performances and, providing a platform for fabricating and developing alginate-based Pickering emulsion-templated materials. Graphical abstract: Generalized 3D printing toward Pickering emulsions stabilized by light-induced telechelic alginate-based amphiphilic derivative. Unlabelled Image